CHANGES IN THE CONFIGURATION OF RUSSIA’S MILITARY PRESENCE IN TAJIKISTAN AND ITS INFLUENCE ON MAINTAINING SECURITY IN CENTRAL ASIA - USMANOV, Jafar (CENTRAL ASIA AND THE CAUCASUS, 2007)
Russia’s military presence in present-day Tajikistan began at the end of the 19th century. The first border units were created in the Pamirs 110 years ago, after the Russian Empire conquered Central Asia in the second half of the 19th century. During the Soviet period, more Soviet army contingents were deployed in Tajikistan. In 1945, the Gatchina 201st motorized rifle division was repositioned on the southern borders of the Soviet Union by a decision of the Union’s supreme leadership. Later, it became part of a limited contingent of Soviet troops in Afghanistan and, after its withdrawal, was deployed once more at its former bases in Tajikistan. In addition to the 201st motorized rifle division, there were also combat units and contingents of the U.S.S.R. Central Asian Border District stationed in the republic. And in 1979, construction began of the Nurek high-altitude opto-electronic center of the Space Monitoring System. It goes without saying that during the Cold War, such an impressive concentration of military might on the Soviet Union’s southern borders fulfilled at least two functions: defense—in the form of moral-psychological restraint of any radical intentions of certain states in the opposing bloc, and preventive-deterrent—permanent control and the possibility of launching a preventive strike in the southern and southwestern directions. A large number of scientific, analytical, and other works have been written today about the consequences of the U.S.S.R.’s collapse, so I will limit myself to saying that the disappearance of the Soviet Union dramatically changed the planet’s geopolitical configuration. When the U.S.S.R. disappeared from the political map of the world and the Commonwealth of Independent States formed in its place, the global strategic significance of a large military contingent, now the Russian Federation’s, in Tajikistan was reduced. Today the question of a possibly earlier change in the configuration of the Russian military presence in the republic, and more precisely, of the withdrawal of regular units of the RF army from it as early as the beginning of the 1990s, is purely hypothetical. History has already dictated its needs. The civil war in Tajikistan and the permanent domestic political instability in neighboring Afghanistan posed real threats to the security of the Central Asian region and the Russian Federation. The common interest of Tajikistan and Russia in ensuring stability and retaining security in the two countries (taking into account the domestic situation in each of them), just as throughout the entire region, was the main driving force behind comprehensive rapprochement between these countries, primarily in the military political sphere. Russian-Tajik cooperation, which grew into a strategic partnership, was reinforced by a mutual agreement on the creation of Russian military base in Tajikistan; and in addition, a large Russian border contingent was stationed there.